Probing optically silent superfluid stripes in cuprates - Rajasekaran, S; Okamoto, J; Mathey, L; Fechner, M; Thampy, V; Gu, G; Cavalleri, A (American Association for the Advancement of Science, 2018)
Unconventional superconductivity in the cuprates coexists with other types of electronic order. However, some of these orders are invisible to most experimental probes because of their symmetry. For example, the possible existence of superfluid stripes is not easily validated with linear optics, because the stripe alignment causes interlayer superconducting tunneling to vanish on average. Here we show that this frustration is removed in the nonlinear optical response. A giant terahertz third harmonic, characteristic of nonlinear Josephson tunneling, is observed in La1.885Ba0.115CuO4 above the transition temperature Tc = 13 kelvin and up to the charge-ordering temperature Tco = 55 kelvin. We model these results by hypothesizing the presence of a pair density wave condensate, in which nonlinear mixing of optically silent tunneling modes drives large dipole-carrying supercurrents.